2000
DOI: 10.1007/pl00009763
|View full text |Cite
|
Sign up to set email alerts
|

The concentrations of Fe, Zn and Co in successive needle age classes of Norway spruce [Picea abies (L.) Karst.]

Abstract: The concentrations of Fe, Zn and Co were determined in up to five successive needle age classes in 54 individual Norway spruce trees from eight different sites (soil pH 3.1-7.7). Fe concentrations (12-25 µg in needles from the current year) were lower than most published values, due to the removal of surface contamination prior to analysis. Fe showed a significant positive correlation with Al. Successive needle age classes either had constant values or showed an increase for Fe concentrations; individual trees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…A similar agreement concerns Cu and Zn, that in polluted environment are mainly exogenous and from root uptake respectively (Nieminen et al, 2004). As concerns Fe deposition on conifer needles, our results seem to parallel those published by Wyttenbach and Tobler (2000). These considerations suggest that, if significant surface concentrations of Mn, Cu, Cr and Pb are detected, these indicate air contamination with that metal.…”
Section: Icp-aessupporting
confidence: 90%
“…A similar agreement concerns Cu and Zn, that in polluted environment are mainly exogenous and from root uptake respectively (Nieminen et al, 2004). As concerns Fe deposition on conifer needles, our results seem to parallel those published by Wyttenbach and Tobler (2000). These considerations suggest that, if significant surface concentrations of Mn, Cu, Cr and Pb are detected, these indicate air contamination with that metal.…”
Section: Icp-aessupporting
confidence: 90%
“…According to Fiedler (1988), the decrease in the Zn concentration was associated with insufficient supply of this element. The results obtained by Wyttenbach and Tobler (2000) showed that any tree with Zn concentration below 20 mg/kg did not reveal an increasing pattern. The content of Zn in current-year needles determined in this study was below 20 mg/kg in only one tree, Trees (2009) The sites: 1-Jodłowice, 2-Gola; general trends were denoted by ''?''…”
Section: Linear Increase In the Elements Concentrationmentioning
confidence: 60%
“…Earlier studies show the ability of Zn to a different behavior in Norway spruce; its concentration in some sites increased with the needle age, whereas in other sites it was characterized by a decreasing tendency (Wyttenbach et al 1995b;Wyttenbach and Tobler 2000). Also Giertych et al (1999) observed concentrations of Zn increasing with age in needles of Pinus nigra only in polluted sites, whereas in unpolluted sites the Zn concentration did not show any clear tendencies.…”
Section: Linear Increase In the Elements Concentrationmentioning
confidence: 75%
See 2 more Smart Citations